DIGITAL CROWDSOURCING UNTUK INFRASTRUKTUR PERKOTAAN: PENDEKATAN TATA KELOLA SMART CITY - Linda Norhan; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar (Jurnal EBI, 2026)
The primary challenge in maintaining infrastructure within developing urban areas is the government's limited capacity to monitor damage in real-time. This study aims to develop and evaluate 'JagaInfra', a web-based platform designed using the Laravel framework as an instrument of social technopreneurship. This research adopts the Design Science Research (DSR) methodology to design a technological artifact that resolves the inefficiency of the reporting bureaucracy. The study highlights how the transformation from manual reporting to a digital crowdsourcing system can enhance public participation. System evaluation results indicate that location validation features (geotagging), distribution map visualization, and transparency in handling status are capable of improving data accountability and public trust. Managerially, JagaInfra offers an effective collaborative governance model within the Smart City ecosystem